2017
DOI: 10.1016/j.jhsa.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Function, Anxiety, and Pain Interference in Nonshoulder Upper Extremity Patients Using the PROMIS Platform

Abstract: Purpose The relationship between psychosocial factors and self-reported physical function among hand and upper extremity patients is complex. The Patient-Reported Outcomes Measurement Information System (PROMIS) platform has attempted to create a variety of specifically-targeted metrics which can be administered using computer adaptive testing (CAT). Three metrics measuring self-reported physical function (herein referred to in combination as “functional” metrics) include the PROMIS Physical Function (PF) CAT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 19 publications
(39 reference statements)
4
18
0
Order By: Relevance
“…10 Similarly, in a study of patients with nonshoulder upper extremity pain, Kazmers and colleagues 9 reported Pearson correlation coefficients between PROMIS-PI and both PROMIS-PF and PROMIS-UE of –0.60 and –0.65, respectively. 9 Similar findings were reported in patients with hallux valgus, in which PROMIS-PI and PROMIS-PF demonstrated a correlation of –0.76, compared with a correlation of –0.44 between PROMIS-Depression and PROMIS-PF. 15 These 3 studies included a largely adult-aged population.…”
Section: Discussionmentioning
confidence: 96%
“…10 Similarly, in a study of patients with nonshoulder upper extremity pain, Kazmers and colleagues 9 reported Pearson correlation coefficients between PROMIS-PI and both PROMIS-PF and PROMIS-UE of –0.60 and –0.65, respectively. 9 Similar findings were reported in patients with hallux valgus, in which PROMIS-PI and PROMIS-PF demonstrated a correlation of –0.76, compared with a correlation of –0.44 between PROMIS-Depression and PROMIS-PF. 15 These 3 studies included a largely adult-aged population.…”
Section: Discussionmentioning
confidence: 96%
“…As such, patients with improved pain are less likely to report perceived disability and impaired function. 34 Improvement in range of motion did not correlate with pain relief. In the present cohort, there was no significant improvement in ROM, and preoperative ROM was well within the functional range of motion of the wrist.…”
Section: Functional and Disability Factorsmentioning
confidence: 93%
“…These values were similar to those previously published in patients with upper extremity injuries, with PROMIS-UE scores ranging from 34 to 37 and PROMIS-PI scores ranging from 57 to 59. 5,11,16 Baseline PROMIS-UE and PROMIS-PI scores in our study showed higher impairment, as only preoperative scores were considered, which provides a clearer picture of what an impaired patient with upper extremity injuries may demonstrate compared with the other cross-sectional correlation studies. The mean PROMIS-D score in this cohort was 48.4, approximately the mean score across the normative population and similar to previously reported PROMIS-D outcomes in patients with upper extremity injuries.…”
Section: Discussionmentioning
confidence: 52%
“…The correlation we found between the PROMIS-UE and PROMIS-PI was similar to that previously reported in patients with upper extremity injuries ( R = –0.60 and –0.65, respectively). 11,16 However, aiming for more generalizable results, those studies included all new, returning, and postoperative patients. The relationship between upper extremity physical function and depression found in our study is unlike previous reports that found depression and patient distress to negatively affect preoperative PROs in patients with rotator cuff injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation